Endocranial anatomy of a new fossil porpoise (Odontoceti, Phocoenidae) from the Pliocene San Diego Formation of California. (July 2014) - Racicot, Rachel A.; Rowe, Timothy
Abstract : The Pliocene fossil porpoise SDSNH 65276 has extremely elongate mandibular morphology, unlike that of any marine amniote, and is superficially most similar to the living bird species known as skimmers ( Rynchops sp .). Endocasts of the pterygoid sinuses and endocranial cavity were digitally segmented from high-resolution X-ray CT scans of the specimen to explore internal anatomy of functionally and phylogenetically important anatomical features of this specimen and odontocetes in general. The sinuses are similar in volume and shape to extant porpoise species, but the dorsal extension of the preorbital lobes are particularly elongate as in the harbor porpoise ( Phocoena phocoena ). The cranial endocast also shows similarities with extant porpoises, but has much deeper interhemispheric fissures, which are filled by ossified meninges, particularly a deep falx cerebri and shallower tentorium cerebelli. Ossifications of these parts of the meninges may reflect faster angular accelerations of the head, deeper diving ability, or both. Penetrations of the endocranial cavity for cranial nerves and blood vessels are like those of extant porpoises. The internal skull morphology of this unique delphinoid sheds additional light both on its phylogenetic affinities and novel odontocete adaptations.